(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3CeG HYO , aEf CaVd GddZGJ , hCMd efWb GdCdSf GdeNJdaGJ eG fRd Hg GdbQBf GdeLjO s
(3BNQgG (B:s
(3BNQg eHJhQ hChd GdehLhO efg (B: (3CKfGA HGH GdNGA hGdhGh eG HYOgeG (B" (3bhdg (B: (3hRYe HYVge Cf Ke ai gPG GdehVhY HeYfi gfGdc hCfgG djSJ GdYWaI , hgPG ZdW dCf Ke HaJM GdKGA HeYfi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi MhGTjgG ebGHdGJs
(3hcJHJ HYV GdYfhGfGJ HGdMeQI s
(3hHYVgG HGdShGO s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs